Making internal feedback explicit: harnessing the comparisons students make during two-stage exams. Issue 4 (11th May 2022) - Nicol, David; Selvaretnam, Geethanjali
Abstract: In two-stage exams, students complete some academic work individually then immediately complete the same work again in small groups. Prior research shows that students perceive the dialogue they engage in at the group stage aids their individual learning. Outcome studies also suggest that engaging in dialogue benefits individual student learning. This investigation takes a different perspective. Learning during two-stage exams is conceptualised as deriving from internal feedback processes, with comparison seen as the mechanism that fuels these processes. To investigate this interpretation, students were asked to write a feedback commentary on their own learning during a two-stage exam. The intention was to make explicit the internal feedback that would naturally occur during the group stage, as students compare their earlier individual performance against the group dialogue and the unfolding group output. Analysis showed that students not only generated content and process feedback but also self-regulatory feedback, and that this feedback was of a higher quality than, and went beyond, the comments the teacher provided. This investigation yields new insights into the nature, scope and power of internal feedback processes, and into how to improve students' learning during such two-stage sequences.